Pengaruh Manajemen Bandwidth Terhadap Skalabilitas Akses Internet di Jaringan LAN - Betalia; Fitriah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The increasing intensity of internet usage in school environments demands optimal network management to ensure stable and high-quality connections. This study aims to evaluate the impact of bandwidth management implementation on the scalability of internet access within the Local Area Network (LAN) at SMKN 5 Seluma, Bengkulu Province. The research employed a descriptive quantitative method with an experimental approach, utilizing the Simple Queue feature on MikroTik devices. Data collection was conducted before and after the implementation, focusing on five key parameters: latency, bandwidth usage, packet loss, the ratio of active users to connection performance, and network availability. The test results showed significant improvements, including a reduction in latency from 144 ms to 52 ms, a decrease in packet loss from 2.58% to 0.5%, and an increase in availability from 94.5% to 99.48%. Statistical testing using the paired t-test confirmed that the differences were significant (p < 0.05). Therefore, the implementation of bandwidth management using the Simple Queue feature has proven effective in improving network efficiency and stability, even under high traffic conditions.